2017
DOI: 10.2217/nnm-2017-0151
|View full text |Cite
|
Sign up to set email alerts
|

Apitherapeutics and phage-loaded Nanofibers As Wound Dressings With Enhanced Wound Healing and Antibacterial Activity

Abstract: The developed biocompatible nanofibers represent competitive wound-healing dressings with potent antibacterial and wound-healing activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…In one study propolis and other honey products were loaded into chitosan nanofibers and tested against multidrug-resistant Pseudomonas aeruginosa. Results demonstrated great biocompatibility, potent antibacterial activity and enhanced wound-healing properties, suggesting their potential use in wound-healing dressings (Sarhan and Azzazy, 2017 ). Propolis extracts contain a wide variety of chemical components including a high content of polyphenols, especially flavonoids which include quercetin, pinocembrin, formononetin, and coumaric acid.…”
Section: Propolismentioning
confidence: 99%
“…In one study propolis and other honey products were loaded into chitosan nanofibers and tested against multidrug-resistant Pseudomonas aeruginosa. Results demonstrated great biocompatibility, potent antibacterial activity and enhanced wound-healing properties, suggesting their potential use in wound-healing dressings (Sarhan and Azzazy, 2017 ). Propolis extracts contain a wide variety of chemical components including a high content of polyphenols, especially flavonoids which include quercetin, pinocembrin, formononetin, and coumaric acid.…”
Section: Propolismentioning
confidence: 99%
“…This novel green nanofibrous dressings showed significant antimicrobial activity against these pathogens, enhanced biocompatibility and wound healing activity, and represented a highly competitive wound dressing. 44 In another study, phage Lysins (PlyPa03 and PlyPa91) were used for the treatment of the CD1 mice model of P. aeruginosa skin infection. The results showed that these two phage lysins (100-µg/mL lysins in 30 mM HEPES buffer) can have an inhibitory effect on this bacterium, even in their stationary phase.…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…However, no significant synergistic activity in reducing the Salmonella count was observed among the three antimicrobials (Wang et al, 2017). Sarhan & Azzazy (2017) and honey alone and in combination was assessed by Oliveira et al (2017). Two Portuguese types of honey with different floral origins and a specific E. coli phage (EC3a) were tested against 24 h and 48 h biofilms.…”
Section: Bacteriophages Associated With Natural Antibacterial Substancesmentioning
confidence: 99%